2009
DOI: 10.1128/jvi.01333-09
|View full text |Cite
|
Sign up to set email alerts
|

The African Swine Fever Virus Virion Membrane Protein pE248R Is Required for Virus Infectivity and an Early Postentry Event

Abstract: The African swine fever virus (ASFV) protein pE248R, encoded by the gene E248R, is a late structural component of the virus particle. The protein contains intramolecular disulfide bonds and has been previously identified as a substrate of the ASFV-encoded redox system. Its amino acid sequence contains a putative myristoylation site and a hydrophobic transmembrane region near its carboxy terminus. We show here that the protein pE248R is myristoylated during infection and associates with the membrane fraction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…Biochemical experiments showed that pB119L is an FAD-containing sulfhydryl oxidase that interacts with a viral protein, A151R. A151R was found to interact with the viral structural protein pE248R, which contains disulfide bridges and belongs to a class of myristoylated proteins related to vaccinia virus L1R (21,22). Vaccinia virus replicates in the cytoplasm of infected cells in contrast to baculovirus nuclear replication.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical experiments showed that pB119L is an FAD-containing sulfhydryl oxidase that interacts with a viral protein, A151R. A151R was found to interact with the viral structural protein pE248R, which contains disulfide bridges and belongs to a class of myristoylated proteins related to vaccinia virus L1R (21,22). Vaccinia virus replicates in the cytoplasm of infected cells in contrast to baculovirus nuclear replication.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are associated with the viral outer membranes and have important roles in the virion assembly process. Examples include the L1R protein in poxviruses (36) and pE248R in ASFV (37). Baculoviruses are morphologically and compositionally distinct from NCLDVs, such that clear counterparts to the NCLDV structural proteins are not evident in baculoviruses (21).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, core delivery depends on viral protein pE248R, an N-myristoylated transmembrane protein located at the inner membrane (18). With use of a conditional lethal mutant, it has been shown that virus assembly and egress occur normally in the absence of pE248R expression.…”
Section: Membrane Fusion and Core Deliverymentioning
confidence: 99%
“…With use of a conditional lethal mutant, it has been shown that virus assembly and egress occur normally in the absence of pE248R expression. However, the pE248R-defective virus progeny is noninfectious due to a postentry blockage (18). When analyzed at the electron microscope level, incoming pE248R-defective particles become disrupted as normal virions but fail to penetrate into the cytosol and accumulate in lysosomes (12).…”
Section: Membrane Fusion and Core Deliverymentioning
confidence: 99%